Surface Remelting of Mold Inserts Made of NC11 Steel - Trytek, Andrzej Stanisław; Tupaj, Mirosław; Majerník, Ján; Gašpár, Štefan; Zbyrad-Kołodziej, Wiktoria; Łysiak, Karol (Journal of Casting & Materials Engineering, 2020)
In the study presented in this paper, the effect of a concentrated heat stream on geometry, microstructure, and hardness of superficial remeltings on NC11 steel is examined. The material is used for disposable mold inserts exposed to intensive abrasive wear in the course of the press-molding of hard aggregate stampings for refractory bricks. As a result of local remelting, the hardness of the steel surface increased and its microstructure was altered. Macro- and microstructure of the remelted areas was examined with the use of optical microscopy and measurements of remelting area geometry were carried out for different parameters of the remelting process. Hardness measurements were taken in the remelting area and in the heat-affected zone. The state of stress in the material before remelting and in the remelted area was also evaluated.